2019
DOI: 10.1186/s13722-019-0137-5
|View full text |Cite
|
Sign up to set email alerts
|

Linking women experiencing incarceration to community-based HIV pre-exposure prophylaxis care: protocol of a pilot trial

Abstract: Background Women experiencing incarceration (WEI) engage in high rates of sex- and drug-related behavior that places them at risk for HIV. Pre-exposure prophylaxis (PrEP) is an efficacious means of reducing HIV acquisition. There is a general lack of knowledge regarding PrEP among women at elevated risk, and only a small percentage of at-risk women are currently engaged in PrEP care. The period of incarceration represents an opportunity to identify at-risk women, initiate PrEP during incarceration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Improved uptake: 77% of patients filled their prescription within a week Miami Veterans Affairs Health System 29,31 Miami, FL General population A hybrid approach where pharmacists provided adherence counseling and monitoring between visits. 42,43 Providence, RI MSW Intervention participants will receive the peer-led strengths-based case management for PrEP initiation and a counseling intervention to address individual barriers to PrEP use PrEP n'Shine 44 Providence, RI TGW Phase 1: peer-led SBCM for PrEP linkage and initiation Phase 2: daily 2-way text messaging reminders with intensive counseling sessions for those with poor adherence RAMP (NCT03256435) 45 Jackson, MS Black YMSM Intervention arm receives SBCM to navigate the PrEP care system MI-NAV (NCT03281343) 46 Northeast, U.S. Incarcerated women 2-phase study-Phase 1: promote PrEP uptake through motivational interviewing; Phase 2: link at-risk women to PrEP care on release Technology-based interventions DOT Mobile app (NCT04633200) 47 Cambridge, MA YMSM Daily PrEP reminders and supportive messages to support adherence DOT diary mobile app (NCT03771638) 48 Atlanta, GA; San Francisco, CA YMSM Integrates artificial intelligence with the smartphone camera to confirm that the individual prescribed PrEP is taking it PrEP iT!…”
Section: General Populationmentioning
confidence: 99%
“…Improved uptake: 77% of patients filled their prescription within a week Miami Veterans Affairs Health System 29,31 Miami, FL General population A hybrid approach where pharmacists provided adherence counseling and monitoring between visits. 42,43 Providence, RI MSW Intervention participants will receive the peer-led strengths-based case management for PrEP initiation and a counseling intervention to address individual barriers to PrEP use PrEP n'Shine 44 Providence, RI TGW Phase 1: peer-led SBCM for PrEP linkage and initiation Phase 2: daily 2-way text messaging reminders with intensive counseling sessions for those with poor adherence RAMP (NCT03256435) 45 Jackson, MS Black YMSM Intervention arm receives SBCM to navigate the PrEP care system MI-NAV (NCT03281343) 46 Northeast, U.S. Incarcerated women 2-phase study-Phase 1: promote PrEP uptake through motivational interviewing; Phase 2: link at-risk women to PrEP care on release Technology-based interventions DOT Mobile app (NCT04633200) 47 Cambridge, MA YMSM Daily PrEP reminders and supportive messages to support adherence DOT diary mobile app (NCT03771638) 48 Atlanta, GA; San Francisco, CA YMSM Integrates artificial intelligence with the smartphone camera to confirm that the individual prescribed PrEP is taking it PrEP iT!…”
Section: General Populationmentioning
confidence: 99%
“…Given the emerging literature, innovative strategies and interventions designed to implement PrEP must consider the relevant factors in uencing PrEP awareness. Speci cally, study ndings underscore the signi cance of various approaches that link adults with incarceration history and HIV risk to comprehensive programs facilitating PrEP access (33,41,42). For example, in people with CJI and HIV risk, Peterson et al found low PrEP awareness and HIV risk perception; yet demonstrated that a program for addiction treatment medication offered by a correctional facility served as a useful pathway to increase PrEP information and may also bolster access and retention upon release (42).…”
Section: Resultsmentioning
confidence: 89%
“…The prevalence of HIV in a concentrated geosocial space has been demonstrated to mediate the in uence of social (e.g., drug use) and structural (e.g., incarceration) factors on individual-level behaviors (e.g., sexual activity, multiple sexual partners, and injection drug use), to the extent that interactions with multilevel factors can create varying pathways of HIV vulnerability for Black adults, especially women (49). Through social interactions with people involved in various criminal justice systems, it is possible that individuals with sexual and drug use behaviors are more vulnerable to HIV, which renders greater individual-level protection and, subsequently PrEP engagement among Black adults at risk (41). While well over half of the sample reported substance use during sex, only a small proportion had ever used PrEP.…”
Section: Resultsmentioning
confidence: 99%
“…These studies aim to improve treatment initiation during incarceration and increase treatment continuation after release to the community. Ramsey et al [8] present a protocol of a pilot study to reduce the risk of HIV infection among incarcerated women. The pilot was designed to increase uptake of pre-exposure prophylaxis (PrEP) during incarceration and linkage to community-based PrEP treatment upon release.…”
Section: Open Accessmentioning
confidence: 99%